Enhancing the Variability of [Ge9] Cluster Chemistry through Phosphine Functionalization. Issue 53 (2nd August 2019) - Wallach, Christoph; Geitner, Felix S.; Klein, Wilhelm; Fässler, Thomas F.
Abstract: The synthetic approach towards molecules that contain Ge atoms with oxidation state 0, and which are exclusively connected to other Ge atoms, is explored by using anionic clusters extracted from binary solids. Besides providing a novel variable method for the introduction of alkenyl moieties to [Ge9 ] cluster compounds, this work expands the spectrum of mixed‐functionalized [Ge9 ] cluster anions, which are suitable for the straightforward synthesis of zwitterionic compounds upon coordination to metal cations. In detail, the synthesis of a series of mixed‐functionalized [Ge9 ] clusters is reported, including [Ge9 {Si(TMS)3 }3 PRR I ] (R= t Bu, R I =(CH2 )3 CH=CH2 ; 2 ) and [Ge9 {Si(TMS)3 }2 PRR I ] − (R and R I : alkyl, alkenyl, aryl, aminoalkyl; 3 a to 11 a, TMS: (trimethyl)silyl). In 2 and 3 a, pentenyl functionalization of the [Ge9 ] clusters was achieved by reaction of the novel chlorophosphine t Bu{(CH2 )3 CH=CH2 }PCl (1 ) with silylated [Ge9 ] clusters. Furthermore, the reactivity of the cluster anions 3 a to 11 a towards NHC Dipp MCl (NHC Dipp =1, 3‐di(2, 6‐diisopropylphenyl)imidazolylidine; M=Cu, Ag) showed a dependency on the steric demand of the phosphine either zwitterions (3 ‐MNHC Dipp to 7 ‐MNHC Dipp ) featuring P–M interactions are formed, or Ge–M coordination (8 ‐MNHC Dipp to 11 ‐MNHC Dipp ) occurs. For M=Ag, the formation of zwitterionic complexes was unequivocally proven by NMR investigations showing 1 J ( 31 P‐ 107 Ag/ 109 Ag) spin‐spin coupling. Abstract : Cluster functionalization : Introducing functional groups through phosphine derivatization of [Ge9 R2 ] 2− and [Ge9 R3 ] − enhances the synthetic potential of [Ge9 ] clusters. Their reactive sites are probed by the attachment of M–NHC + groups (see figure; M=Cu, Ag; NHC=N‐heterocyclic carbene).